A very human being: Sister Marie Simone Roach, 1922–2016. Issue 4 (28th October 2016) - Villeneuve, Michael J; Tschudin, Verena; Storch, Janet; Fowler, Marsha D M; Peter, Elizabeth
Abstract : Sister (Sr.) Marie Simone Roach, of the Sisters of St. Martha of Antigonish, Nova Scotia, died at the Motherhouse on 2 July 2016 at the age of 93, leaving behind a rich legacy of theoretical and practical work in the areas of care, caring and nursing ethics. She was a humble soul whose deep and scholarly thinking thrust her onto the global nursing stage where she will forever be tied to a central concept in nursing, caring, through her Six Cs of Caring model. In Canada, she was the lead architect of the Canadian Nurses Association's first code of ethics, and her influence on revisions to it is still profound more than 35 years later. In this paper, four global scholars in nursing and ethics are invited to reflect on Sr. Simone's contribution to nursing and health‐care, and we link her work to nursing and health‐care going forward.1